Patients with Advanced Ovarian Cancer Administered Oral Etoposide following Taxane as Maintenance Chemotherapy - Hiroaki Nagano; Yasunari Tachibana; Megumi Kawakami; Mariko Ueno; Yoshihiro Morita; Mitsue Muraoka; Koichiro Takagi (Case Reports in Oncology, 2016)
Introduction: The concept of maintenance therapy is one of the highly relevant approaches in the management of advanced ovarian cancer. The fundamental goal of maintenance therapy is to improve survival outcomes. We attempted to reinforce maintenance chemotherapy by adding oral etoposide following taxane administration. Cases: We retrospectively evaluated 14 patients with advanced ovarian cancer who had achieved clinically defined complete response to a primary platinum/taxane chemotherapy regimen and who were administered oral etoposide (50 mg/day × 21 days per cycle monthly for 3-5 cycles) following paclitaxel or docetaxel administration as maintenance chemotherapy. With regard to oral etoposide toxicity, grade 2 oral mucositis and grade 3 anemia were observed in 1 patient each. Three to five cycles of etoposide were administered to all patients, though daily dosage was reduced to 25 mg in 2 patients due to toxicity. The median progression-free survival was 43.5 months, the median overall survival was 86 months, and 5-year overall survival was 77.1%. Conclusion: The results from this ovarian cancer treatment evaluation suggest that oral etoposide may be administered safely following paclitaxel or docetaxel as maintenance chemotherapy. We expect this regimen to contribute to the improvement in the survival outcomes of patients with advanced ovarian cancer.